2006
DOI: 10.1148/radiol.2383050146
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Evaluation of Acute Appendicitis in Pregnancy

Abstract: MR imaging is an excellent modality for use in excluding acute appendicitis in pregnant women who present with acute abdominal pain and in whom a normal appendix is not visualized at US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(128 citation statements)
references
References 28 publications
6
118
0
4
Order By: Relevance
“…MRI has been reported to obtain good results for excluding or detecting appendicitis [13][14][15][16][17]19]. Our prospective study in a large group of patients confirms that MRI yields excellent diagnostic results and markedly decreases the negative appendectomy rate, without an increase in perforation rate.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…MRI has been reported to obtain good results for excluding or detecting appendicitis [13][14][15][16][17]19]. Our prospective study in a large group of patients confirms that MRI yields excellent diagnostic results and markedly decreases the negative appendectomy rate, without an increase in perforation rate.…”
Section: Discussionsupporting
confidence: 79%
“…Technological developments have made ultrafast sequences possible, resulting in shorter examination times and fewer motion artifacts. Detection of appendicitis with MRI has been published in a small group of pregnant and non-pregnant patients [13][14][15][16][17][18][19]. This is, to our knowledge, the first prospective blinded clinical study, in more than 100 patients, to evaluate MRI in patients clinically suspected of having appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…28 Several studies have reported non-visualization of the appendix in a large percentage of pregnant women with suspected appendicitis. [29][30][31][32][33] However, in a review of studies on the value of ultrasound diagnostics during appendicitis in pregnancy, sensitivity ranged from 67 to 100% and specificity of 83 to 96%, compared with the general population, in which sensitivity and specificity were 86 and 96%, respectively. 34 Several factors influence the performance of ultrasound diagnosis of appendicitis in pregnancy, including gestational age, body mass index (BMI), and most importantly, the training and experience of the examiner.…”
Section: 28mentioning
confidence: 99%
“…Si el apéndice mide entre 6 y 7 mm de diámetro, presenta contenido de alta señal T2 pero no se identifican cambios inflamatorios en el tejido adiposo o engrosamiento de sus paredes, se debe realizar seguimiento de la paciente, al ser los hallazgos no concluyentes (Figura 2a,b) Se ha descrito una sensibilidad de 100% y especificidad de 94% en el diagnóstico de apendicitis durante el embarazo mediante RM (4) . …”
Section: Apendicitis Agudaunclassified